RISK FACTORS OF CARDIOVASCULAR DISEASES IN TEACHING STAFF AMONG PRIMARY SCHOOLS OF TOMSK CITY (THE DATA FROM MULTICENTER PROSPECTIVE PREVENTION STUDY) - N. S. Karamnova; V. N. Serebryakova; I. N. Trubacheva; V. S. Kaveshnikov; V. A. Vygodin; А. М. Kalinina (Кардиоваскулярная терапия и профилактика)
Aim. To study the prevalence of risk factors (RF) of cardiovascular diseases (CVD) in the teaching staff of primary schools in Tomsk city. Material and methods. Totally 154 teachers studied (staff of 2 general education schools of Tomsk) at the age of 21-71 y. Mean age 46,6±10,9. Response — 84%. Results. Prevalence of arterial hypertension (AH) among the staff was 51,9%, and primary onset of AH — in 3,2%. Less than a half of teachers with AH took antihypertension therapy (42,8%) and just in 15% of those we found target levels of blood pressure during business day. Prevalence of smoking was 7,0%. We found a high prevalence of alimentary CVD risk factors. Two thirds of the staff were overweight (68,8%). Prevalence of excessive bodyweight was 33,1% and of obesity — 35,7%, of abdominal obesity — 40,2%. In teaching staff there was high level of hyperglycemia (12,1%), hypercholesterolemia (78,0%) and hypertriglyceridemia (32,0%). Insufficient physical activity was noted in 30% of teachers. Conclusion. The main points are found for the development and implementation of preventive strategies in the group — effective control over AH and correction of alimentary-dependent RF of CVD.